2014
DOI: 10.1016/j.celrep.2014.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA Methylation Patterns by CK2-Mediated Phosphorylation of Dnmt3a

Abstract: DNA methylation is a central epigenetic modification that is established by de novo DNA methyltransferases. The mechanisms underlying the generation of genomic methylation patterns are still poorly understood. Using mass spectrometry and a phosphospecific Dnmt3a antibody, we demonstrate that CK2 phosphorylates endogenous Dnmt3a at two key residues located near its PWWP domain, thereby downregulating the ability of Dnmt3a to methylate DNA. Genome-wide DNA methylation analysis shows that CK2 primarily modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…Deplus et al showed that CK2 phosphorylates Ser386 and Ser389 located near the CK2 PWWP domain, which is the conserved Pro-Trp-Trp-Pro motif, and inhibits the ability of the PWWP domain to promote DNA methylation (25). As explained above, we found that d-flow significantly increased PKCf activation.…”
Section: Dnmt Phosphorylation and Methylationsupporting
confidence: 71%
See 1 more Smart Citation
“…Deplus et al showed that CK2 phosphorylates Ser386 and Ser389 located near the CK2 PWWP domain, which is the conserved Pro-Trp-Trp-Pro motif, and inhibits the ability of the PWWP domain to promote DNA methylation (25). As explained above, we found that d-flow significantly increased PKCf activation.…”
Section: Dnmt Phosphorylation and Methylationsupporting
confidence: 71%
“…AKT and PKC can phosphorylate DNMT1, and AKT1-mediated Ser143 DNMT1 phosphorylation stabilizes DNMT1 and decreases the ability of DNMT1 to associate with PCNA and UHRF1, which are involved in sustaining DNA methylation patterns through the recruitment of DNMT1 (29). Recently, Deplus et al investigated the role of casein kinase II (CK2) in regulating Dnmt3a activity (25). CK2 is a serine/threonine kinase, which is constitutively active and ubiquitously expressed in all mammalian tissue and cell types (30,90,123).…”
Section: Dnmt Phosphorylation and Methylationmentioning
confidence: 99%
“…Cell Line 4D-Nucleofector X KitLonzaCat# V4XC1012 Deposited Data Raw data (ChIP-seq and BLESS)This paperArrayExpress: E-MTAB-5817RAD51 and XRCC4 ChIP-seqAymard et al., 2014ArrayExpressE-MTAB-1241RNA polymerase II S2P ChIP-seqCohen et al., 2018ArrayExpressE-MTAB-6318MethylCap-seqDeplus et al., 2014GEO GSE26810 Experimental Models: Cell Lines DIvA cellIacovoni et al., 2010N/AU20S-ISceI GFP-RFP (NHEJ)Jacquet et al., 2016N/A3xFlag-Twin-strep-tagged SUPT7L K562Dalvai et al., 2015N/AU2OSN/AATCC HTB-96, RRID:CVCL_0042 Oligonucleotides HR-DSB1 for ChIP-qPCRFW GATTGGCTATGGGTGTGGACREV CATCCTTGCAAACCAGTCCTAymard et al., 2014N/AHR-DSB2 for ChIP-qPCRFW CCGCCAGAAAGTTTCCTAGAREV CTCACCCTTGCAGCACTTGAymard et al., 2014N/ANHEJ-DSB for ChIP-qPCRFW TGCCGGTCTCCTAGAAGTTGREV GCGCTTGATTTCCCTGAGTAymard et al., 2014N/AACTB for ChIP-qPCRFW AGCCGGGCTCTTGCCAATREV AGTTAGCGCCCAAAGGACCAThis paperN/ATAF12 for ChIP-qPCRFW GCTGAGACGAACGCTTCACTREV CCTTCGAACACTGACCCACTThis paperN/AsiRNA siSUPT7L-46 CUACUAGACCCAACAGAAA[dT] [dT] UUUCUGUUGGGUCUAGUAG[dT] [dT]This paperN/AsiRNA siSUPT7L-47 CUAUCACAGUUACAUGCUA[dT] [dT]UAGCAUGUAACUGUGAUAG[dT] [dT]This paperN/AsiRNA siKAT2B (PCAF) CUCUAAUCCUCACUCAUUU[dT] [dT]AAAUGAGUGAGGAUUAGAG[dT] [dT]This paperN/AsiRNA siKAT2A (GCN5) GCUACUACGUGACCCGGAA[dT] [dT]UUCCGGGUCACGUAGUAGC[dT] [dT]This paperN/A Recombinant DNA pX330-LMNAgRNA1Pauty et a...…”
Section: Methodsmentioning
confidence: 99%
“…HDAC inhibitors (HDACi), such as MS275 (entinostat) and SAHA (vorinostat), are able to maintain or restore the acetylation status of histone and non-histone targets and may thus have important therapeutic applications. Some of these inhibitors have already been used as antitumor agents, 5,6 showing significant activity against a variety of both hematological and solid tumors at relatively well-tolerated pharmacological doses. [7][8][9] Although little is known about the specific role of HDACs during hematopoiesis, altered HDAC activity has been directly linked with genesis of acute promyelocytic leukemia (APL) [10][11][12] and other types of leukemias.…”
Section: Introductionmentioning
confidence: 99%